Biological Remediation of Cyanide: A Review - Ibrahim, Karamba Kabiru; Syed, Mohd Arif; Shukor, Mohd Yunus; Ahmad, Siti Aqlima (BIOTROPIA, 2016)
Cyanide and its complexes are produced by industries all over the world as waste or effluents. Biodegradation is considered to be the cheapest and the most effective method to get rid of cyanide in the environment. Several studies on different types of microorganisms that can degrade cyanide in the environment have been carried out. Hydrolytic, oxidative, reductive, and substitutive/transfer reactions are some of the common pathways used by microorganisms in cyanide degradation. Biodegradation of cyanide can occur aerobically or an-aerobically depending on the environmental conditions. Immobilised enzymes or microorganisms prove to be very effective method of degradation. Microorganisms such as Klebsiella oxytoca, Corynebacterium nitrophilous, Brevibacterium nitrophilous, Bacillus spp., Pseudomonas spp. and Rhodococcus UKMP-5M have been reported to be very effective in biodegradation of cyanide.